1990
DOI: 10.1029/ja095ia08p11957
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field structure of interplanetary magnetic clouds at 1 AU

Abstract: Interplanetary magnetic clouds, although not dominant, are a relatively common feature of the solar wind at 1 AU. Their diameters at 1 AU fall in the range of 0.2–0.4 AU, and they have enhanced field strength (B ≃ 15–30 nT at 1 AU), and lower plasma temperature and density than the surrounding plasma. The internal field is a magnetic force‐free configuration, and therefore the current density (J) is proportional to B everywhere: J = α B, giving ▽×B = α B. If α is constant throughout the cloud (Burlaga, 1988), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
891
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 819 publications
(941 citation statements)
references
References 19 publications
24
891
1
1
Order By: Relevance
“…The plasma b has a low value (Figure 1d) inside the structure, and the smooth IMF rotation is marked in Figure 1e. These properties make this CME qualify as a magnetic cloud (MC) [Burlaga et al, 1981;Lepping et al, 1990].…”
Section: Magnetosheath Flows and Magnetopause Shape: Case Studymentioning
confidence: 99%
“…The plasma b has a low value (Figure 1d) inside the structure, and the smooth IMF rotation is marked in Figure 1e. These properties make this CME qualify as a magnetic cloud (MC) [Burlaga et al, 1981;Lepping et al, 1990].…”
Section: Magnetosheath Flows and Magnetopause Shape: Case Studymentioning
confidence: 99%
“…Burlaga [1988] suggested to use for this approximation a force-free cylindrical solution with constant c• found by Lundquist [1950]. Lepping et al [1990] presented fits for 18 magnetic clouds based on this approximation. They concluded that these fits matched the rotation of the magnetic field vector quite well, but it was not so good for the magnetic field magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…As further confirmation that both spacecraft saw the same cloud, the magnetic field measured in the cloud at each spacecraft was fit using a force-free model of the magnetic field [Lepping et al, 1990]. Table 1 bCloud axis longitude (GSE coordinates).…”
mentioning
confidence: 99%